ANALISIS IMPLIKASI HUKUM PELANGGARAN HAK PRIVASI DI MEDIA SOSIAL BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 2024 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Alexander Raja Parulian Pasaribu; Armunanto Hutahaean; Yuni Artha Manalu (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Rapid technological advancements have significantly changed various aspects of society, especially through the development of information and communication technology. Social media makes it easy for individuals to communicate and share information, but this convenience also increases the risk of privacy violations. Privacy violations occur when personal data is misused or disseminated without consent, infringing on an individual’s right to privacy and potentially leading to criminal acts. This thesis uses a normative juridical method, with data collected through literature studies. The role of the government is crucial in addressing privacy violations on social media. However, public participation is also needed to support prevention efforts. Individuals or corporations that violate privacy rights can be held criminally responsible for their actions. Legal accountability for such violations is based on Indonesia’s Criminal Code (KUHP) and Law No. 19 of 2016 concerning Information and Electronic Transactions (ITE Law). These laws provide a legal foundation for prosecuting those who misuse personal data and ensuring the protection of citizens’ privacy in the digital age.